Analysis and optimization of resistance characteristics of submarine snorkel air-intake valve - Hu Haibin; Zhou Rui; Zhou Zhe; Liu Yijun (Zhongguo Jianchuan Yanjiu, 2019)
[Objectives]It is important to optimize the structure of the air-intake valve for submarine snorkel and reduce air intake resistance,which is of great significance to submarine energy saving and working safety.[Methods]The CFD method is used to simulate the resistance characteristics of the air-intake valve,and the accuracy of the calculation results is verified by experiments. The two parameters flapper stroke and the intake angle are adjusted and analyzed,and the related rules between the air-intake valve resistance and the structure are obtained.[Results]The research results show that the pressure loss of the air-intake valve gradually decreases with the increase of the flapper stroke. When the flapper stroke h is greater than 244 mm,continuing to increase the flapper stroke does not contribute much to the reduction of pressure loss. When the intake angle θ is greater than 65°,the air-intake valve pressure loss will rise sharply;when the intake angle is less than 65°,the angle change will have little effect on the pressure loss.[Conclusions]The research shows that the flapper stroke and the intake angle have important influence on the air-intake valve resistance characteristics. By structural optimization,the intake resistance of the air-intake valve is significantly reduced,and the results can be guidance for engineering design.